Field Relevant Variation in Ambient Temperature Modifies Density-Dependent Establishment of Plasmodium falciparum Gametocytes in Mosquitoes - Pathak, Ashutosh K.; Shiau, Justine C.; Thomas, Matthew B.; Murdock, Courtney C. (Frontiers in Microbiology, 2019)
The relationship between Plasmodium falciparum gametocyte density and infections in mosquitoes is central to understanding the rates of transmission with important implications for control. Here, we determined whether field relevant variation in environmental temperature could also modulate this relationship. Anopheles stephensi were challenged with three densities of P. falciparum gametocytes spanning a 10-fold gradient, and housed under diurnal/daily temperature range (“DTR”) of 9⁰C (+5⁰C and –4⁰C) around means of 20⁰C, 24⁰C and 28⁰C. Vector competence was quantified as the proportion of mosquitoes infected with oocysts in the midguts (oocyst rates) or infectious with sporozoites in the salivary glands (sporozoite rates) at peak periods of infection for each temperature to account for the differences in development rates. In addition, oocyst intensities were also recorded from infected midguts and the overall study replicated across three separate parasite cultures and mosquito cohorts. While vector competence was similar at 20 DTR 9⁰C and 24 DTR 9⁰C, oocyst and sporozoite rates were also comparable, with evidence, surprisingly, for higher vector competence in mosquitoes challenged with intermediate gametocyte densities. For the same gametocyte densities however, severe reductions in the sporozoite rates was accompanied by a significant decline in overall vector competence at 28 DTR 9⁰C, with gametocyte density per se showing a positive and linear effect at this temperature. Unlike vector competence, oocyst intensities decreased with increasing temperatures with a predominantly positive and linear association with gametocyte density, especially at 28 DTR 9⁰C. Oocyst intensities across individual infected midguts suggested temperature-specific differences in mosquito susceptibility/resistance : at 20 DTR 9⁰C and 24 DTR 9⁰C, dispersion (aggregation) increased in a density-dependent manner but not at 28 DTR 9⁰C where the distributions were consistently random. Limitations notwithstanding, our results suggest that variation in temperature could modify seasonal dynamics of infectious reservoirs with implications for the design and deployment of transmission-blocking vaccines/drugs.